Hacia un plan de acción para los primates mesoamericanos - Rodríguez-Luna, Ernesto; Cortés-Ortiz, Liliana; Mittermeier, Russell; Rylands, Anthony; Wong-Reyes, Grace; Carrillo, Eduardo; Matamoros, Yolanda; Nuñez, Félix; Motta-Gill, Johanna (Neotropical Primates, 1996)
No abstract